Kompetencja emocjonalna kobiet i mężczyzn a życie w rodzinie - Filipiak, Grażyna (Wydawnictwo Naukowe UAM, 2001)
The article focuses on the differences in emotional competence of women and men. The author, on the basis of numerous studies, discusses family life’s influence on constituting these differences. Such variables as: marital status, ability to express emotions by partners, ability to talk about emotions, care of health both one’s own and of the family members, dealing in fate situations, response to partner’s death, suicidal tendency and the higher death rate of men. It is shown that during the socialisation processes in the family men acquire worse emotional competencies than women. They are less able to recognise their own and others’ emotions and to react to them in the emotionally adequate way as well. Men’s lower emotional resourcefulness is accompanied by the higher need to profit from the positive aspects of family life. The family has also a greater impact on men’s than on women’s psychophysical sphere.
Women’s and men’s emotional competence and family life